Analisis Laporan Keuangan dalam Mengukur Kinerja Keuangan pada PT. Astra Agro Lestari Tbk. - Riris Vina Marito Situmorang; Jani Puspita Sari; Junita Fina Rebekka Tamba; Hamonangan Siallagan (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
Financial reports are a very important tool in the business world because they provide transparent information about the financial health of a company. One way to better understand financial reports is to analyze the company's financial ratios. This analysis helps map various key aspects of a company's operations and financial performance, from liquidity and profitability to operational efficiency and capital structure. This research analyzes the company's financial reports to assess the financial performance of PT Astra Agro Lestari Tbk in the last few years, in terms of financial ratio analysis. The aim of this research is to use financial ratio analysis techniques to provide an overview of the company's financial health, operational efficiency and capital management strategies implemented.